Production functions for samples of rice farms in West Malaysia - Abdul Halim Ismail, (Universiti Kebangsaan Malaysia, 1972)
This paper reports an investigation into the production functions for samples of wet rice farms for Sabak Bernam, Kuala Selangor, North Malacca and Kota Bharu for the main season of 1966. The Cobb-Douglas function has been estimated in all cases, with land and labour as explanatory variables for the functions for Sabak Bernam and Kuala Selangor, and land, labour and fertilisers for the functions for North Malacca and Kota Bharu. The coefficients for land input have been found in all cases to be relatively high. These are significant at the 1-percent level. Of the coefficients for labour input only that for North Malacca has been found significant at the 1-percent level. The coefficient for fertilisers for North Malacca is also significant at the same level. The marginal products for all the inputs are calculated. An attempt it also made to compare the marginal value products with the available information on the prices of the respective input. Finally the results obtained are compared with the findings of some studies of rice farms in a number of neighbouring countries.